Pengembangan Model “YUDI” dalam Pembelajaran Karakter SD - Purnamasari, Veryliana; Hernanda, Ardiyanto (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2017)
The problem behind the absence of a traditional game-based gymnastics development model that can support the development of character in elementary school. Another thing that lies behind this research, the various acts of moral decline and character, especially in elementary school students who have reached low grade elementary students. The goal to be achieved through this research is to produce "Yudi" model in character education education in elementary school. The method that will be applied in achieving that goal is Borg & Gall's research and development model. This research focuses on the development of Buyung's gymnastics model and traditional games that can be used in character learning in elementary school. The object chosen in this research is elementary school students in Semarang City. Determination of data source is done by purposive. The results of this study is a learning model "Yudi" which combines “Si Buyung” and traditional games to build character. Data of product feasibility evaluation result is an expert validation sheet. Expert assessment results show that the "Yudi" model that has been developed is feasible according to the material expert and the learning expert. The "Yudi" model developed to build a caring character is considered feasible to be used according to an excellent material expert with a total validation score of 78 so that the "Yudi" model developed for character building is judged worthy of use. According to the excellent value of "Yudi" model with a total validation score of 80 indicating the model "Yudi" is worth using.